Calibration aspects of the JEM-EUSO mission - Adams, J. H. (2015)
he JEM-EUSO telescope will be, after calibration, a very accurate instrument which yields the number of received photons from the number of measured photo-electrons. The project is in phase A (demonstration of the concept) including already operating prototype instruments, i.e. many parts of the instrument have been constructed and tested. Calibration is a crucial part of the instrument and its use. The focal surface (FS) of the JEM-EUSO telescope will consist of about 5000 photo-multiplier tubes (PMTs), which have to be well calibrated to reach the required accuracy in reconstructing the air-shower parameters. The optics system consists of 3 plastic Fresnel (double-sided) lenses of 2.5 m diameter. Theaim of the calibration system is to measure the efficiencies (transmittances) of the optics and absolute efficiencies of the entire focal surface detector. The system consists of 3 main components: (i) Pre-flight calibration devices on ground, where the efficiency and gain of the PMTs will be measured absolutely and also the transmittance of the optics will be. (ii) On-board relative calibration system applying twomethods: a) operating during the day when the JEM-EUSO lid will be closed with small light sources on board. b) operating during the night, together with data taking: the monitoring of the background rate over identical sites. (iii) Absolute in-flight calibration, again, applying two methods: a) measurement of the moon light, reflected on high altitude, high albedo clouds. b) measurements of calibrated flashes and tracks produced by the Global Light System (GLS). Some details of each calibration method will be described in this paper.